Cardiac Fibroma with Asymptomatic Ventricular Arrhythmia in an Adolescent with Gorlin's Syndrome - Menon, Dipika; Dentel, John N.; Sanil, Yamuna; Lawrence, David (Journal of Pediatric Genetics, 2021)
Nevoid basal cell carcinoma syndrome (NBCCS), also referred to as Gorlin's syndrome, is an autosomal dominant inherited condition that predisposes affected individuals to various tumors such as cardiac fibromas. Though technically benign, cardiac fibromas may result in malignant arrhythmias and sudden death. The pertinent literature pertaining to pediatric cases of cardiac fibromas and their clinical features were reviewed. We present the case of an asymptomatic teenage with de novo NBCCS who was diagnosed with both NBCCS and cardiac fibroma later in life. The patient was noted to have clinically significant ventricular arrhythmias that were eliminated with tumor resection. There are no established best practice guidelines for the management of cardiac fibromas in patients with NBCCS. Given the risk of sudden arrhythmic death, the presence of ventricular arrhythmias should prompt strong consideration of tumor resection.
Keywords: Gorlin's syndrome; fibroma; nevoid basal cell carcinoma syndrome